INTERNATIONAL COOPERATION AS A TOP-PRIORITY ACTIVITY OF THE UNIVERSITY - Oleg N. Belenov (Высшее образование в России)
The article analyzes the importance of international cooperation in higher education on the example of Voronezh State University. One of the university's goals in the sphere of international relations is to develop and introduce innovative academic programmes in cooperation with leading international partner universities. The University pays special attention to the development of academic mobility and student and faculty exchange programs. Voronezh State University has over 158 partnership agreements with the leading universities all over the world.